Plant Salinity Stress Response and Nano-Enabled Plant Salt Tolerance - Li, Zengqiang; Zhu, Lan; Zhao, Fameng; Li, Jiaqi; Zhang, Xin; Kong, Xiangjun; Wu, Honghong; Zhang, Zhiyong (Frontiers in Plant Science, 2022)
The area of salinized land is gradually expanding cross the globe. Salt stress seriously reduces the yield and quality of crops and endangers food supply to meet the demand of the increased population. The mechanisms underlying nano-enabled plant tolerance were discussed, including (1) maintaining ROS homeostasis, (2) improving plant’s ability to exclude Na+ and to retain K+, (3) improving the production of nitric oxide, (4) increasing α-amylase activities to increase soluble sugar content, and (5) decreasing lipoxygenase activities to reduce membrane oxidative damage. The possible commonly employed mechanisms such as alleviating oxidative stress damage and maintaining ion homeostasis were highlighted. Further, the possible role of phytohormones and the molecular mechanisms in nano-enabled plant salt tolerance were discussed. Overall, this review paper aims to help the researchers from different field such as plant science and nanoscience to better understand possible new approaches to address salinity issues in agriculture.